A Qualitative Study of Antibiotic Use Practices in Intensive Small-Scale Farming in Urban and Peri-Urban Blantyre, Malawi: Implications for Antimicrobial Resistance - Mankhomwa, John; Tolhurst, Rachel; M'biya, Eunice; Chikowe, Ibrahim; Banda, Pemphero; Mussa, Jimmy; Mwasikakata, Henry; Simpson, Victoria; Feasey, Nicholas; MacPherson, Eleanor E. (Frontiers in Veterinary Science, 2022)
The routine uses of antimicrobials in meat production have been identified as a driver of AMR in both animals and humans. Significant knowledge gaps exist on antibiotic use practices in farming in low-income contexts, particularly in sub-Saharan Africa. This paper sought to generate evidence on antibiotic use practices in food animals in urban- and peri-urban Blantyre. We used a qualitative research methodology to provide an in-depth understanding of the types of antibiotics being used in scavenging and small-scale intensive farming of food animals, if and how they were used in and why we see this pattern of use. The qualitative methods included: medicine-use survey (130) with a range of households who kept feed animals; key informant interviews with a range of participants including farmers, community based veterinary officers and vet shop workers (32); and Key-Informant interviews (17) with policy makers, regulators, and academics; and 6-months of ethnographic fieldwork, on farms, with households engaged in farming, with vet officers and vet stores. Our findings suggest antibiotic use was more common in households that used small-scale intensive farming practices, and rare in households that did not. Antibiotics were used prophylactically and to treat disease and were often considered vital for farmers to stay afloat in a precarious economic and social environment. Farmers faced significant challenges in accessing veterinary services. Antibiotics were dispensed, prescribed, and administered by a range of actors including veterinary officers, veterinary stores, and farmers. A complex regulatory framework governed the import, prescription, and administration of antibiotics. Despite this, veterinary stores provided easy access to antibiotics, including colistin, an antibiotic on the WHO’s critically important antibiotics for human health. Our findings speak to the need for a holistic approach to interventions to optimise the use of antibiotics in animal farming in Malawi. Improving farmers’ access to affordable veterinary services, providing information about correct antibiotic use including withdrawal periods and feed supplementation, as well as improvements in regulation (nationally and internationally) and enforcement could lead to antibiotic use being optimised in animals.